Does the pursuit of perfection by Chinese people harm interpersonal relationships? Evidence from the Wenjuan - Zhang, Jun; Luo, Xiaoyan; Yang, Wanshu; Xu, Jie; Deng, Ping; Wu, Hui; Guo, Junqiao (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the mechanisms of the relationship between Perfectionism and interpersonal relationships.MethodsData were collected and research was conducted using the online platform Wenjuanxing, which distributed the Psychological Resilience Scale, Core Self-Evaluation Scale, Interpersonal Sensitivity Questionnaire, Perfectionism Scale, and Peer Relationships Scale.ResultsPerfectionism not only directly and significantly predicts interpersonal sensitivity, but it can also mediate interpersonal sensitivity through dual or triple mediation paths formed by Psychological Resilience, Peer Relationships, and Core Self-Evaluation.ConclusionPerfectionism can directly and significantly predict interpersonal sensitivity and can also indirectly predict interpersonal sensitivity through Psychological Resilience, Peer Relationships, and Core Self-Evaluation. The traditional Confucian educational philosophy in China advocates core values such as “benevolence,” “righteousness,” “propriety,” and “wisdom,” emphasizing that individuals should constantly cultivate themselves and their families to achieve moral perfection. This can lead to heightened interpersonal sensitivity and severe psychological repression. Modern education should build on traditional educational values while promoting inclusivity and tolerance, encouraging individuals to focus on the present, accept their emotions and experiences, respect human freedom of development, and safeguard psychological health.